Organizational ethics indicators in Iranian hospital: An importance-performance analysis - Amir Ahmad Shojaei; Bahareh Mahbanooei; Amin Farahani; Ali Asghar Pourezzat (Wolters Kluwer Medknow Publications, 2023)
Background: Organizational ethics focuses on the importance of how organizations behave when faced with specific situations and decisions. This study aims to identify and prioritize organizational ethics indicators in Imam Khomeini Hospital Complex (IKHC) in Iran. Materials and Methods: This was a mixed-method research project. To recognize hospital ethics indicators, 18 semistructured interviews were conducted and 38 indicators were identified through thematic analysis. In the next stage, a quantitative approach was adopted to use the importance-performance matrix for data analysis. This part was a descriptive survey with a statistical population consisting of nurses, medical, clinical, and administrative staff. The questionnaire was distributed using the random sampling method, and a total of 349 samples were collected. Results: Based on the interviews and open coding, 73 themes were identified for organizational ethics indicators and classified into two main groups: "ethics drivers in hospital" and "personal ethics." After measuring content validity, 35 indicators of organizational ethics in IKHC were examined in terms of importance and performance. The results showed that nine indicators had high importance and poor performance, 11 had high importance and performance, nine had low importance and performance, and finally six indicators had low importance and high performance, and according to these findings, practical suggestions were put forward. Conclusions: Based on the identified indices and by applying importance-performance analysis, it is recommended to continually assess the status of ethics in hospitals and offer strategies for improving organizational ethics.